Move to stay: genetic structure and demographic history of a wolf spider inhabiting coastal sand dunes of southern South America. Issue 7 (3rd October 2019) - Postiglioni, Rodrigo; Bidegaray-Batista, Leticia; Simó, Miguel; Arnedo, Miquel A.
Abstract : Dispersal ability can enhance the probability of an organism surviving and reproducing, and affects the geographic structure of its genetic variability. Allocosa senex is a nocturnal sand-dwelling wolf spider strictly associated with oceanic, estuarine and freshwater sandy coast habitats of southern South America, including Uruguay, Brazil, and Argentina. Recent research has revealed the presence of diverse dispersal strategies, both aerial and aquatic. Here we investigated the genetic structure and demographic history of A. senex using sequences of the mitochondrial genome and genomic scanning using amplified fragment length polymorphisms (AFLPs). We hypothesized the presence of a weak population genetic structure in space because of high levels of gene flow. We analysed individuals from 21 localities from Uruguay, Argentina, and Brazil. We obtained 60 sequences for the cox1 (17 haplotypes) and 445 AFLP polymorphic loci of 90 individuals. The results were in agreement with our hypothesis. They revealed an absence of spatially structured genetic diversity, neither among localities nor among basins, suggesting little isolation by distance in the group. The mitochondrial gene tree was dated and age estimates revealed a recent origin of A. senex, which was traced back to the Middle Pleistocene. Both the mitochondrial star-like topology and the departures from neutrality, further supported by the lack of AFLP population structure and isolation by distance, are in agreement with a recent population expansion. Demographic changes could be related to climatic oscillations and geological changes undergone by the study area during the Pleistocene.